The specific PKC-α inhibitor chelerythrine blunts costunolide-induced eryptosis - Ghashghaeinia, Mehrdad; Koralkova, Pavla; Giustarini, Daniela; Mojzikova, Renata; Fehrenbacher, Birgit; Dreischer, Peter; Schaller, Martin; Mrowietz, Ulrich; Martínez-Ruiz, Antonio; Wieder, Thomas; Divoky, Vladimir; Rossi, Ranieri; et al. (Apoptosis, 2020)
Costunolide, a natural sesquiterpene lactone, has multiple pharmacological activities such as neuroprotection or induction of apoptosis and eryptosis. However, the effects of costunolide on pro-survival factors and enzymes in human erythrocytes, e.g. glutathione and glucose-6-phosphate dehydrogenase (G6PDH) respectively, have not been studied yet. Our aim was to determine the mechanisms underlying costunolide-induced eryptosis and to reverse this process. Phosphatidylserine exposure was estimated from annexin-V-binding, cell volume from forward scatter in flow cytometry, and intracellular glutathione [GSH]i from high performance liquid chromatography. The oxidized status of intracellular glutathione and enzyme activities were measured by spectrophotometry. Treatment of erythrocytes with costunolide dose-dependently enhanced the percentage of annexin-V-binding cells, decreased the cell volume, depleted [GSH]i and completely inhibited G6PDH activity. The effects of costunolide on annexin-V-binding and cell volume were significantly reversed by pre-treatment of erythrocytes with the specific PKC-α inhibitor chelerythrine. The latter, however, had no effect on costunolide-induced GSH depletion. Costunolide induces eryptosis, depletes [GSH]i and inactivates G6PDH activity. Furthermore, our study reveals an inhibitory effect of chelerythrine on costunolide-induced eryptosis, indicating a relationship between costunolide and PKC-α. In addition, chelerythrine acts independently of the GSH depletion. Understanding the mechanisms of G6PDH inhibition accompanied by GSH depletion should be useful for development of anti-malarial therapeutic strategies or for synthetic lethality-based approaches to escalate oxidative stress in cancer cells for their sensitization to chemotherapy and radiotherapy.
Keywords: glukosa-6-fosfátdehydrogenasa; oxidační stres; Calcium; reaktivní formy kyslíku; Chelerythrine; Phosphatidylserine exposure; vápník; Benzophenanthridines; Glucosephosphate Dehydrogenase; benzofenantridiny; Enzyme Inhibitors; Sesquiterpenes; seskviterpeny; Reactive Oxygen Species; glutathion; eryptóza; lidé; Costunolide; Eryptosis; Humans; Glucose-6-phosphate dehydrogenase (G6PDH); erytrocyty; Erythrocytes; apoptóza; Glutathione; Protein Kinase C-alpha; Oxidative Stress; inhibitory enzymů; Apoptosis; proteinkinasa C-alfa